Waterton-Glacier International Peace Park - Petersen, David, 1946- (Chicago : Childrens Press, 1992)
Depicts the wildlife, mountains, glaciers, wildfowers, and other sights protected by the Waterton-Glacier Park, an international park created in 1932 by the Canadian and American governments.
Includes index.
Keywords: National parks and reserves; Waterton-Glacier International Peace Park (Mont. and Alta.) -- Juvenile literature; Waterton-Glacier International Peace Park (Mont. and Alta.)